2023
DOI: 10.3390/agriculture13071457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agricultural Production Trusteeship on Agricultural Carbon Emission Reduction

Xiaoyan Sun,
Shuya Guang,
Jingjing Cao
et al.

Abstract: Based on the survey data of five large grain-producing provinces in China, this paper studies the effect of agricultural production trusteeship on agricultural carbon emission reduction by using a propensity score matching method. The empirical results show that the carbon emission of wheat reduces by 7.107 kg/mu, with a decrease rate of 15.5% after participating in agricultural production trusteeship. Among them, chemical fertilizers, manpower input, agricultural chemicals and diesel oil, respectively, reduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Based on the analysis of the influencing factors of black land protection, Qu et al demonstrated that green agricultural production can promote black land conservation tillage [40]. The proposal of "Agricultural Production Trusteeship Service-Application of Green Production Technology-Agricultural Carbon Emission Reduction" mechanism can better analyze the internal interaction process between black land protection and green agricultural production trusteeship [41]. Research has proved that the enhancement of soil carbon sequestration capacity is an important indicator for the improvement of black soil quality [2].…”
Section: Research On the Relationship Between Black Land Protection A...mentioning
confidence: 99%
“…Based on the analysis of the influencing factors of black land protection, Qu et al demonstrated that green agricultural production can promote black land conservation tillage [40]. The proposal of "Agricultural Production Trusteeship Service-Application of Green Production Technology-Agricultural Carbon Emission Reduction" mechanism can better analyze the internal interaction process between black land protection and green agricultural production trusteeship [41]. Research has proved that the enhancement of soil carbon sequestration capacity is an important indicator for the improvement of black soil quality [2].…”
Section: Research On the Relationship Between Black Land Protection A...mentioning
confidence: 99%